Pendampingan Pekerjaan Semenisasi Jalan Alwi Jamaludin II Dusun III Desa Pulau Gadang Kecamatan XIII Koto Kampar - Sabri, Muhammad Riyan; Putra, Agus Alisa (Journal of Social and Community Service, 2024)
Community service is the embodiment of academics being present within society, involving the academic community, including students, lecturers, alumni, and educational staff. Community service is an effort to implement the Tri Dharma of Higher Education, specifically the aspect of community service, which is inseparable from the other two dharmas. Pulau Gadang Village has infrastructure where 50% of the neighborhood roads in each hamlet are damaged and have not been cemented. There is a need for guidance to produce high-quality mixtures and to instill a culture of road maintenance among the community. The implementation method involves an approach through communication to provide direction in carrying out the cementing work in Pulau Gadang Village.